THE RELATIONSHIP BETWEEN RELIGIOSITY AND RESILIENCE IN MEDICAL STUDENTS - Amir, Zulfadli Akbar; Rumiani, Rumiani (Islamic Psychology Study Program, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This study aims to determine the relationship between religiosity and resilience in medical students. The hypothesis proposed in this study is that there will be a positive correlation between religiosity and resilience in medical students. The scale used for data collection uses the Resilience Scale compiled by Bochaver et al, (2021) based on theory from Connor and Davidson (2003) and the Religiosity Scale uses the IIUM Religiosity Scale (IIUMRelS) compiled by Diana Mahudin, Noraini Noor and Mariam Adawiah Dzulkifli (Mahudin et al., 2016). The subjects used in this study were 219 medical students, male or female, with a minimum age of 18 to 25 years. The results found in this study show a correlation coefficient of r = 0.530 with a significance of p <0.001. The data obtained from this study show that there is a positive relationship between religiosity and resilience in medical students. Religiosity makes an effective contribution of 28.1% towards the resilience of medical faculty students. This concludes that the hypothesis in this study was accepted.